The affects of caching in browser stage on the performance of web items delivery - Yasin, Waheed; Ibrahim, Hamidah; Abdul Hamid, Nor Asilah Wati; Udzir, Nur Izura (The Society of Digital Information and Wireless Communications (SDIWC), 2013)
Network congestion remains one of the main barriers to the continuing success of the Internet. Caching is a way to reduce traffic load on the server and network backbone, which improves the efficiency and scalability of web items delivery. Caching in computer networks might be performed in different stages. In this article, we investigate the load that web pages can put on a network and how caching can reduce the bandwidth requirements. This article concludes that caching in browser stage improves the delivery of web items.